ISDN concepts, facilities and services - Kessler, Gary C. (McGraw-Hill series on computer communications, 1996)
Written in a clear, straightforward style, this edition now features entirely new chapters on national ISDN; broadband and Fast Packet services; Frame Relay call control signaling; Frame Relay applications, products, and services; ATM call control signaling; ATM applications, products, and services; and Internet access and ISDN. You'll also find greatly expanded material on AIN (Advanced Intelligent Network); ISDN